ANALISIS TINGKAT KEPUASAN KONSUMEN (STUDI KASUS PADA RIJSTTAFEL RESTORAN OASIS, JAKARTA) - Agung Gita Subakti; Aditya - Pratomo; Mia Pia Adiati (Jurnal Hospitality dan Pariwisata, 2017)
Oasis Restaurant was one of two restaurant that is consistent with the concept of using Rijsttafel service since 1976, A presentation in serving many kinds of Indonesian Cuisine, presented by 12 waitress wearing kebaya (a traditional Indonesian dress) that is the combination between Dutch culture and Indonesia. There are plenty of guests that dine here. Foreigner or local people, even lots of distinguished guest such as President and Royal Family, Famous peoples who also experiencing in dining here. On the other hand, with so many restaurants there are currently serving various kinds of food service diverse also prompting competitions among restaurants itself. Oasis Restaurant need to realize how important the customer satisfaction in order to survive the competitions. Therefore, researchers want to analyze the level of customer satisfaction through products and service given to the customers. Research method used is descriptive associative. With this research, we are expecting that Oasis Restaurant would be able to know the level of their customer satisfaction as a way to improve the quality of their products and services. Keywords : Customer Satisfaction, Product Quality, Service